2018
DOI: 10.20945/2359-3997000000018
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Thyroid Imaging Reporting and Data System (TI-RADS), and ultrasonographic classification of the American Thyroid Association (ATA) in differentiating benign from malignant thyroid nodules

Abstract: Both TI-RADS and the ATA guidelines have high sensitivity and NPV for the diagnosis of thyroid carcinoma. These systems are feasible for clinical application, allowing to better select patients to undergo fine-needle aspiration biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 34 publications
(40 reference statements)
5
21
2
Order By: Relevance
“…The main limit of guidelines proposed by international societies derives from the lack of specificity, mostly at highest categories. In fact, we confirm that they all have high sensitivity but low specificity ( 18 , 21 , 28 ). Accordingly, malignancy rate remains between 41 and 50% even in the highest risk class, with possible consequent over-medicalization and unnecessary FNA.…”
Section: Discussionsupporting
confidence: 74%
“…The main limit of guidelines proposed by international societies derives from the lack of specificity, mostly at highest categories. In fact, we confirm that they all have high sensitivity but low specificity ( 18 , 21 , 28 ). Accordingly, malignancy rate remains between 41 and 50% even in the highest risk class, with possible consequent over-medicalization and unnecessary FNA.…”
Section: Discussionsupporting
confidence: 74%
“…The risk of cancer in TI-RADS 2 is reported to be 0%, and the risk of cancer in TI-RADS 3 is reported to be 2-4%. In other studies, the expected malignancy rate in TI-RADS 3 was 0.7% [16,17] [9,13,18] In our study, malignancy was 0% in post-operative pathology reports in TI-RADS 2-3 cases. The risk of cancer was reported to be 6-17% in patients with a TI-RADS score of 4 [8].…”
Section: Discussionsupporting
confidence: 56%
“…Although there have been a few studies that have compared different risk stratification systems [21][22][23][24], and in particular, the ATA and ACR-TIRADS systems [25,26], to our knowledge, this is the first study to evaluate the performance of these two systems using raters from multiple clinical disciplines. We found that both ATA and ACR TI-RADS risk stratifications systems exhibited similar diagnostic performance and interobserver agreement, although ATA guidelines were more accurate in predicting the malignancy risk for each risk stratum in our study population.…”
Section: Discussionmentioning
confidence: 99%